Association between isolated diastolic hypertension and cardiovascular events: a systematic review and meta-analysis of prospective cohorts. (14th October 2021) - Huang, M; Tang, T; Cheng, X
Abstract: Background: Isolated diastolic hypertension (IDH) is a subtype of hypertension, which is defined as systolic blood pressure (SBP) <140 mmHg and diastolic blood pressure (DBP) ≥90 mmHg by 2018 European Society of Cardiology (ESC) guideline and 2019 National Institute for Health and Care Excellent (NICE). Whereas some previous studies have demonstrated the significant association between IDH and cardiovascular (CV) events, some have not. Purpose: To assess the association between IDH and the risk of CV events, CV mortality, and all-cause mortality. Methods: We conducted a systematic search for publications using Medline, Embase, and the Cochrane Library from inception through March 2021 for prospective cohort studies exploring the association between IDH and CV events, CV mortality, and all-cause mortality. Relative risks (RR) or hazard ratios were extracted from the selected studies. Random effect models with inverse variance weighting were used to calculate the pooled RR and 95% confidence interval (CI). The primary outcome was a composite of total CV events including CV mortality. The secondary outcomes were CV mortality and all-cause mortality. We defined the IDH as SBP <140 mmHg and DBP ≥90 mmHg, reference group as BP less than 140/90mmHg. Results: Overall, 15 studies were identified including 1049587 participants (5.5% IDH). For the primary outcome, IDH was significantly associated with risk of CV events (RR, 1.40 [95% CI, 1.18–1.66], p<0.001). The increased risk of CV events was also observed in subgroup analyses based on age (less or more than 50) and sex. However, in further stratified analysis based on geographical region, only the Asia population showed a significant association with increased risk of CV events, whereas results were null in Europe and North America populations. For the secondary outcomes, IDH was significantly associated with increased CV mortality (RR [95% CI], 1.41 [1.12–1.78], p<0.001) but not with all-cause mortality (RR [95% CI], 1.13 [0.86–1.48], p=0.378). The sensitivity analysis showed the overall results did not vary significantly after exclusion of any one study. Conclusions: IDH is associated with increased risk of CV events and CV mortality. Further, more large-scale prospective epidemiological cohorts are needed to confirm our conclusion. FUNDunding Acknowledgement: Type of funding sources: None.